Examining the knowledge work of person-centred care: Towards epistemic reciprocity. (February 2023) - Dell'Olio, M.; Whybrow, P.; Reeve, J.
Abstract: Objective: It is increasingly recognised that when healthcare staff fails to give adequate credence to patients' illness-related knowledge work, this epistemic injustice undermines person-centred care. Therefore, we set out to examine the experiences of people with long-term conditions with knowledge work in healthcare settings to identify changes needed to strengthen person-centred primary care. Methods: We designed a qualitative study and recruited people with long-term conditions in the UK. We conducted individual interviews (analysed using interpretive phenomenological analysis) and focus groups (analysed using thematic analysis), then integrated findings from both methods through an approach focused on their complementarity. Results: Participants described how successful person-centred consultations were characterised by a negotiation between patient and doctor and moments of broad exploration, reflexive listening, and reciprocal enquiry, which allowed for epistemic reciprocity. Conclusions: Epistemic reciprocity is a core component of person-centred clinical consultations, fostering the co-creation of new knowledge of patient experience and need through the interactive knowledge work of patient and doctor. Practice implications: Medical education could benefit from initiatives that develop knowledge use and integration skills across primary care professionals. Accommodating for patient's and doctor's knowledge work during clinical practice requires redesigning the consultation process, including timing, headspace, pre-consultation, and post-consultation work. Highlights: Qualitative study to explore the knowledge work of person-centred primary care. Consultations need broad exploration, reflexive listening and reciprocal enquiry. Epistemic reciprocity is needed for clinical consultations to be person-centred. Healthcare redesign needs to allow for patient and doctor reflexive knowledge work.